Characterization of a Fusarium poae world-wide collection by using molecular markers - Dinolfo, María Inés (2014)
Fusarium poae has been considered as a minor species among those that cause Fusarium Head Blight (FHB) disease but in recent years several researchers have documented a high frequency of occurrence of this species. In this study, a total of 173 F. poae isolates from Argentina, Belgium, Canada, England, Finland, France, Germany, Hungary, Italy, Luxembourg, Poland, Switzerland and Uruguay were evaluated by using inter simple sequence repeats (ISSR) and amplified fragment length polymorphism (AFLP) to evaluate genetic variability within F. poae and to amplify MAT idiomorphs as a possible mechanism that could explain part of the variability found in this species. The molecular analysis obtained from both molecular markers showed a high intraspecific variability. However, a partial clustering between F. poae isolates and their geographic origin was obtained by ISSR markers while AFLP showed isolates from different geographic locations distributed throughout the dendrogram. Moreover, ISSR grouped all the F. poae isolates into a different cluster from the F. langsethiae and F. sporotrichioides isolates used as outgroups compared with the dendrogram obtained using AFLP markers. Analysis of molecular variance (AMOVA) indicated a high genetic variability in the F. poae collection, with most of the genetic variability resulting from differences within, rather than between, American and European populations by using both molecular markers. Regarding MAT idiomorphs, for most F. poae isolates both MAT-1 and MAT-2 were present from each isolate.